Comparative Exercise Physiology: A Worldwide Goal - Felipe, Gomes Ferreira Padilha (Journal of Sports and Exercise Medicine, 2018)
This perspective advocates comparative exercise physiology across species to advance understanding of performance, adaptation, and health applications.